Vagus nerve stimulation modulates arachidonic acid production in the mesenteric lymph following intestinal ischemia-reperfusion injury. Issue 4 (October 2021) - Nakatsutsumi, Keita; Morishita, Koji; Yagi, Masayuki; Doki, Sanae; Watanabe, Arisa; Ikegami, Nahoko; Kobayashi, Testuyuki; Kojima, Mitsuaki; Senda, Atsushi; Yamamoto, Kouhei; Aiboshi, Junichi; Coimbra, Raul; et al.
Abstract : BACKGROUND: Inflammatory lipid mediators in mesenteric lymph (ML), including arachidonic acid (AA), are considered to play an important role in the pathogenesis of multiple-organ dysfunction after hemorrhagic shock. A previous study suggested that vagus nerve stimulation (VNS) could relieve shock-induced gut injury and abrogate ML toxicity, resulting in the prevention of multiple-organ dysfunction. However, the detailed mechanism of VNS in lymph toxicity remains unclear. The study aimed to investigate the relationship between VNS and inflammatory lipid mediators in ML. METHODS: Male Sprague-Dawley rats underwent laparotomy and superior mesenteric artery obstruction (SMAO) for 60 minutes to induce intestinal ischemia followed by reperfusion and observation. The ML duct was cannulated, and ML samples were obtained both before and after SMAO. The distal ileum was removed at the end of the observation period. In one group of animals, VNS was performed from 10 minutes before 10 minutes after SMAO (5 V, 0.5 Hz). Liquid chromatography–electrospray ionization–tandem mass spectrometry analysis of AA was performed for each ML sample. The biological activity of ML was examined using a monocyte nuclear factor κ-light-chain-enhancer of activated B cells activation assay. Western blotting of phospholipase A2 group IIA (PLA2 -IIA) was also performed for ML and ileum samples. RESULTS: Vagus nerve stimulation relieved the SMAO-induced histological gut injury. The concentration of AA and level of nuclear factor κ-light-chain-enhancer of activated B cells activation in ML increased significantly after SMAO, whereas VNS prevented these responses. Western blotting showed PLA2 -IIA expression in the ML and ileum after SMAO; however, the appearance of PLA2-IIA band was remarkably decreased in the samples from VNS-treated animals. CONCLUSION: The results suggested that VNS could relieve gut injury induced by SMAO and decrease the production of AA in ML by altering PLA2 -IIA expression in the gut and ML.